Lethal dose and clinical signs of Streptococcus agalactiae in Javanese medaka (Oryzias javanicus Bleeker 1854) - Mastor, Siti Suhaiba; Azmai, Mohammad Noor Amal; Ismail, Ahmad; Saad, Mohd Zamri; Nasruddin, Nurrul Shaqinah (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2016)
This study was conducted to determine the lethal dose and clinical signs of Streptococcus agalactiae in Javanese medaka. Javanese medaka was collected in Sungai Pelek, Sepang and brought to the laboratory for acclimatization. The fish were then challenged from 102 - 108 CFU/ml of S. agalactiae via intraperitoneal injection. Mortalities and clinical signs were observed until 10 days of exposure, while the dead fish were collected for bacterial isolation and histological analyses. Lethal dose 50% (LD50) of S. agalactiae in Javanese medaka was determined at 6.5 × 103 CFU/mL. Most of the infected fish showing lethargy, erratic swimming, exophthalmia, opacity and necrosis at the injection site. The histopathological changes were mainly generalised congestion of the internal organs. Streptococcus agalactiae were successfully isolated from the dead fish. Results showed that Javanese medaka was susceptible towards S. agalactiae infection and could be a potential alternative organism for study of streptococcocis in fish.